Gender Differences in Stress Related Disorders among the Ukrainian Military in the War-zone - Frankova, Ірина; Chaban, Олег; Burlaka , Олена; Lahutina, Софія; Fedotova, Зоя (Psychosomatic Medicine and General Practice, 2019)
Introduction. Recent years, both Ukraine and European countries have experienced an abrupt increase in the number of traumatic events and unexpected social changes. This correlates with an increased risk of stress related disorders prevalence. The risk factors for post-traumatic stress disorder include the female gender and type of trauma (man-made). The hormonal status of a woman (oral contraceptives usage) is poorly studied, but is a promising preventive factor for PTSD. Aim. To identify clinically significant difference in post-stress gender reactions and assess the impact of chronic and acute combat stress on the mental and psychosomatic state of the military. Results. At the first stage, military in the war zone were examined (n = 47), 64% were men, mean age was 33 ± 8.3 y. o ., and the average duration of military service was 11.5 months. Men were characterized by an increased levels of guilt, physical aggression, the frequency and amount of alcohol consumption, and occurrence of obsessive-compulsive symptoms, the prevalence of PTSD was 20%. Among women, there was an increase in the levels of resentmen, hostility, anxiety, depression and the severity of stress, high body mass index, the prevalence of PTSD was 23.5% -25.9%. The decrease in the quality of life in women was associated with biological anhedonia (sex, living conditions, physical condition), with social anhedonia (lack of self-realization at work or in society) in men. At the second stage of research, the purpose of which was to assess the psychosomatic effect of combat stress on reproductive function, 54 women aged 33.4 ± 8 y. o. were examined. Half of the women in the service from 1 to 2 years planed a pregnancy, in 5.5% the pregnancy was confirmed by a gynecologist. Women who used oral contraceptives had the highest quality of life levels; PTSD was absent in this category of women. Women whose contraceptive method was barrier (condoms), or they were in menopause had the highest levels of post-traumatic stress and poor quality of life. Gynecological complications were three times more often in women with PTSD. Women had a desire to build a military career and at the same time a desire to become a mother. As a result, this splitting leads to failure in both areas and is often accompanied by psychosomatic problems, such as the inability to get pregnant. Conclusions. The response to stress due to psychological trauma is gender-specific, women are at greater risk of mental health issues. Understanding the gender specific characteristics of a stress response leads to targeted and more effective treatment of PTSD. Future studies should pay particular attention to the hormonal status of women. Research of possible PTSD predictors and effective early intervention strategies right after exposure to trauma is one of the key goals of psychiatry and medical psychology nowadays.